2011
DOI: 10.2478/v10038-011-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Muscle Strengthening on Neuro-Musculo-Skeletal Dynamics in A Squat Jump: A Simulation Study

Abstract: Purpose. The aim of this study was to quantitatively investigate the effects of muscle strengthening in a vertical squat jump based on a neuro-musculo-skeletal model and a forward dynamics simulation. Methods. During simulation trials, 16 major muscle groups of the lower extremities were gradually strengthened up to 20%. Results. Complex yet systematic deviations in body kinematics, kinetics and the neural control pattern were observed as a result of gradual muscle strengthening. Conclusions. based on the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Repeated jump testing involving 5 assessments occurred before an additional rested baseline test in the afternoon was completed and following a 3-6 days of recovery period. As such, learning effects and possibly diminished fatigue induced by repeated jump testing may have positively influenced mechanisms associated with a heightened SJ performance (i.e., timing of muscle activation (1,3,4,26)) during the subsequent afternoon test. Data indicate that proficiency in technically demanding tasks (i.e., SJ test ( 29)) may remove its potential masking effect on diurnal changes in performance (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated jump testing involving 5 assessments occurred before an additional rested baseline test in the afternoon was completed and following a 3-6 days of recovery period. As such, learning effects and possibly diminished fatigue induced by repeated jump testing may have positively influenced mechanisms associated with a heightened SJ performance (i.e., timing of muscle activation (1,3,4,26)) during the subsequent afternoon test. Data indicate that proficiency in technically demanding tasks (i.e., SJ test ( 29)) may remove its potential masking effect on diurnal changes in performance (28).…”
Section: Discussionmentioning
confidence: 99%
“…The period of inactivity separating the repeated jump testing protocol and completion of the afternoon test may also have positively influenced intermuscular coordination and thus SJ performance (26), possibly because of diminished fatigue (2). Findings from previous research have indicated that residual fatigue after repeated jump testing separated by limited recovery periods may obscure possible diurnal variation (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation